A Novel Application of Ti-Substituted Polyoxometalates: Anti-Inflammatory Activity in OVA-Induced Asthma Murine Model - Dong Li; Xiuzhu Gao; Jingmin Gu; Yuan Tian; Yaqing Liu; Zheng Jin; Dongmei Yan; Ya-Guang Chen; Xun Zhu (Bioinorganic Chemistry and Applications)
Objective. Asthma is a chronic inflammatory disorder. Despite extensive researches into the treatment and management of it, current treatments and management strategies are still limited. The search for a novel approach to its treatments is urgently needed. Researches on the potential medical use of polyoxometalates (POMs) have already shown it has antiviral and antitumor bioactivities. But the effects of POM in immune systems are still largely unknown. Methods. In order to investigate the role of POM in the asthmatic disease, we used OVA-induced asthma murine model and observed the pathological changes between mice that received three different Ti-substituted POMs (0.3 μg per mouse per dose) when challenged with OVA. We also measured the type 2 cytokine expressions to reveal the potential mechanism. Results and Conclusions. Our results showed that two Ti-substituted POMs, K5H2[FeW11TiO40]·17H2O and K5H[H2ZnW11TiO40]·35H2O, could reduce OVA-induced lung inflammation, serum IgE level (around 2000 ng/mL to less than 1000 ng/mL), leukocytes infiltration in the lung, and cytokines levels (including IL-4, IL-5, IL-13, and TNF-α) but Ti-centered POM K4[TiW12O40]·10H2O did not. Thus, Ti-substituted POMs may have pharmaceutical values especially in treatments for asthmatic diseases.